Autophagy Inhibition Enhances the Anti-Tumor Activity of Methylseleninic Acid in Cisplatin-Resistance Human Lung Adenocarcinoma Cells - Xin, Ming; Gao, Qi; Xiang, Xindong; Xu, Juanjuan; Jiao, Yuhan; Li, Xuan; Zhang, Xianzhen; Jia, Xiuqin (Frontiers in Pharmacology, 2022)
Cisplatin (DDP)-based chemotherapy remains one of the standard treatment options for patients with advanced lung adenocarcinoma (LUAD), and cisplatin resistance is the biggest challenge to this therapy. Autophagy is also closely associated with chemoresistance in LUAD. Desperately need to find a way to improve the treatment efficiency of cisplatin-resistant LUAD in clinical practice. Previous studies reported that methylseleninic acid (MSA) has good anti-proliferation and pro-apoptotic activities in tumor cells. However, the effectiveness of MSA on cisplatin-resistant LUAD and its effect on the induction of autophagy is still unclear. In the current study, we found that MSA effectively inhibited the proliferation of LUAD cell lines and triggered mitochondrial pathway-mediated apoptosis. This effect was more pronounced in cisplatin-resistant LUAD cells with high MDR1 expression. In contrast, the mitochondrial damage caused by MSA treatment can be degraded by inducing selective autophagy in LUAD cells, thereby exerting a self-protective effect on tumor cells. Mechanistically, MSA inhibits proliferation, promotes apoptosis, and induces autophagy in LUAD cells by inhibiting of the Akt/mTOR pathway. Combination with autophagy inhibitors reduces the effect of this selective autophagy-induced resistance, and thus enhancing even more the anti-tumor effect of MSA on cisplatin-resistant LUAD cells. Finally, We speculate that MSA in combination with autophagy inhibitors may be a promising new therapeutic strategy for the treatment of cisplatin-resistant LUAD.